2020
DOI: 10.1002/nop2.738
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of social media and in‐person interventions for low back pain conditions in nursing personnel (SMILE)

Abstract: Aim To compare two educational approaches to reduce low back pain in nurses. Design A community randomized controlled clinical trial. Methods Data were collected with two interventions and a control arm between August 2018 and January 2019. Participants were recruited from three hospitals. Hospital 1 received an in‐person educational programme, Hospital 2 received via the website and Hospital 3 received nothing. Statistical analysis was carried out with a follow‐up of 3 and 6 months. Results A total of 180 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…showed that educational intervention that is accompanied by repetition and reminder is more successful and effective [28] .…”
Section: Discussionmentioning
confidence: 99%
“…showed that educational intervention that is accompanied by repetition and reminder is more successful and effective [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Of the 6435 unique records identified, 537 full texts were reviewed, and 27 included in the review ( Fig 1 ). Most trials were conducted in the United States [ 39 48 ], followed by three in the United Kingdom [ 49 – 51 ], two each in Spain [ 52 , 53 ], Sweden [ 54 , 55 ], and Thailand [ 56 , 57 ], and one each in Australia [ 58 ], Croatia [ 59 ], Finland [ 60 ], Germany [ 61 ], Iran [ 62 ], the Netherlands [ 63 ], and New Zealand [ 64 ]. One trial was conducted in both Denmark and Norway [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of present study showed 54.85% of patients had moderate pain and 25.8% suffered from mild pain. Previous studies demonstrated an appropriate educational intervention can help patients to promote their preventive health behaviors and decrease their LBP [31][32][33][34][35] . Evidences showed pain intensity affected the QOL and could decrease it [31,36] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated an appropriate educational intervention can help patients to promote their preventive health behaviors and decrease their LBP [31][32][33][34][35] . Evidences showed pain intensity affected the QOL and could decrease it [31,36] . In this study, findings extracted from the SF-36 questionnaire displayed that there was a significant correlation between pain intensity and almost all of the QOL dimensions except social functioning.…”
Section: Discussionmentioning
confidence: 99%